Debating Identity: Reflections on Coverage of Dharaharā and Kāṣṭhmaṇḍap Post Gorkha-Earthquake 2015 - Rajopadhyaya, Abhas Dharananda (Bodhi: An Interdisciplinary Journal, 2019)
The 7.8 Mw Gorkhā-earthquake in April 2015, took 8,857 lives, injured 21,952, destroyed 755,549 buildings, 581 heritages and cost an estimated approximate 513.38 billion. Many heritage sites, including those enlisted in the World Heritage Site, were damaged due to this disaster. The fall of Dharaharā, among all cultural-historical sites, was given (un- ) due attention by many national media, owing to high number of deaths and as a popular landmark of the city. This modern elite tower structure was presented as symbol of national unity and of ’rising back’. But there are other important public heritages too - many centuries older than Dharaharā and they too had stories of deaths, of injuries and of survivals, but received a very small space or almost none in the national media. I take an example of Kāṣṭhamaṇḍap that hosted over 54 people during the earthquake. I have used the method of qualitative content analysis to discuss the construction of identity by national media.